PENGARUH MEKANISME CORPORATE GOVERNANCE DAN KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN LQ 45 - Thaharah, Nina; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2016)
The purpose of this researchis to examine the influence of Good Corporate Governance to the managerial ownership, institutional ownership, independent directors, audit committees and financial performance to the LQ45 firm value. The population is all companies which are listed in Indonesian Stock Exchange (IDX). The samples are all LQ45 companies which are listed in Indonesia Stock Exchange during 2011-2014 periods. The total samples are 18 LQ45 companies which have been determined by using purposive sampling. The method of analysis of this research has been done by using multiple regressions analysis technique. The result of the research shows the managerial ownership has no influence to the firm value, that Institutional ownership has an influence to the firm value, the board of independent commissioner has an influence on the firm value, the audit committee has an influence to the firm value, return on asset does not have any influence to the firm value, and return on equity has an influence on firm value.Keywords: Good Corporate Governance, Financial Performance, Firm Value